Judging the Decalogue: The Ten Commandments and the Establishment Clause - Astoria, Ross Stephen (ProQuest Dissertations & Theses, 2010)
Beginning in 1999 the Federal Courts experienced a great influx of litigation over the constitutionality of a government's display of the Ten Commandments. This dissertation examines the causes and consequences of this litigation. In the first part of the dissertation I examine changes in Establishment Clause doctrine which first make a government's display of religious symbols a possible subject of litigation and, later, make the Decalogue an attractive symbol for conservatives to defend before the federal judiciary. In the second part of the dissertation I examine two counties from Tennessee who elected to post the Ten Commandments and were subsequently sued by the ACLU. I conclude that participants to either side of the conflict situate their political and legal activity in mythic conceptions of American Republicanism. Both posting the Ten Commandments and the resistance to such posting are attempts to preserve or return to these mythic conceptions. The last part of the dissertation is normative jurisprudence. Using the results from parts one and two I offer suggestion as to how the Supreme Court might alter its doctrine so as to align it with the value of equal citizenship. In this regard, Establishment Clause jurisprudence emphasizes the distinction between religious purposes and secular purposes. This distinction ought to be muted. Instead, the Supreme Court should promulgate doctrine designed to protect equal citizenship.